2014
DOI: 10.3389/fped.2014.00111
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temperature and Anesthetic Agents on Ciliary Function in Murine Respiratory Epithelia

Abstract: Background: Mucus transport mediated by motile cilia in the airway is an important defense mechanism for prevention of respiratory infections. As cilia motility can be depressed by hypothermia or exposure to anesthetics, in this study, we investigated the individual and combined effects of dexmedetomidine (dex), fentanyl (fen), and/or isoflurane (iso) at physiologic and low temperatures on cilia motility in mouse tracheal airway epithelia. These anesthetic combinations and low temperature conditions are often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
6
27
0
1
Order By: Relevance
“…The VCSEL D‐OCT device measured a CBF value at physiologic temperature of approximately 9 Hz, which is similar to that reported in other ex vivo tissue studies . Pharmacologic agents and temperature are known to augment CBF in ex vivo mucosal samples; although we diminished CBF using 10% formalin, we also expect D‐OCT to reproduce the known correlation between temperature or pharmacological agents and CBF reported in the literature . In the future, the ability of D‐OCT to monitor changes in CBF due to these conditions will be evaluated ex vivo and in vivo.…”
Section: Discussionsupporting
confidence: 81%
“…The VCSEL D‐OCT device measured a CBF value at physiologic temperature of approximately 9 Hz, which is similar to that reported in other ex vivo tissue studies . Pharmacologic agents and temperature are known to augment CBF in ex vivo mucosal samples; although we diminished CBF using 10% formalin, we also expect D‐OCT to reproduce the known correlation between temperature or pharmacological agents and CBF reported in the literature . In the future, the ability of D‐OCT to monitor changes in CBF due to these conditions will be evaluated ex vivo and in vivo.…”
Section: Discussionsupporting
confidence: 81%
“…2). Consistent with prior literature, 22 flow speeds increase as temperature increases from room to body temperature. Interestingly, after returning the temperature to a normal range of 36 to 38°C from febrile temperatures, flow velocities do not recover to baseline values for that temperature range.…”
supporting
confidence: 89%
“…Memarzadeh et al reported higher water intake in ventilated cages compared with CCs in a mouse study but did not address the gender of the animals or the temperature 13. It has also been observed that the temperature inside the cages tends to be higher than that outside the cages 14. Therefore, the temperature in the IVCs may be higher than that in the CCs because the lids of IVCs are closed, unlike those of CCs.…”
Section: Discussionmentioning
confidence: 99%